MEF2A Is the Trigger of Resveratrol Exerting Protection on Vascular Endothelial Cell - Liu, Benrong; Pang, Lihua; Ji, Yang; Fang, Lei; Tian, Chao Wei; Chen, Jing; Chen, Changnong; Zhong, Yun; Ou, Wen-Chao; Xiong, Yujuan; Liu, Shi Ming (Frontiers in Cardiovascular Medicine, 2022)
Both resveratrol and myocyte enhancer factor 2A (MEF2A) may protect vascular endothelial cell (VEC) through activating the expression of SIRT1. However, the relationship between resveratrol and MEF2A is unclear. We aimed to investigate the deeper mechanism of resveratrol in protecting vascular endothelial cells and whether MEF2A plays a key role in the protective function of resveratrol. Human umbilical vein endothelial cell (HUVEC) was used for in vitro study, and small interfere RNA was used for silencing MEF2A. Silencing MEF2A in the vascular endothelium (VE) of ApoE−/− mice was performed by tail injection with adeno associated virus expressing si-mef2a-shRNA. The results showed that treatment of HUVEC with resveratrol significantly up-regulated MEF2A, and prevented H2O2-induced but not siRNA-induced down-regulation of MEF2A. Under various experimental conditions, the expression of SIRT1 changed with the level of MEF2A. Resveratrol could rescue from cell apoptosis, reduction of cell proliferation and viability induced by H2O2, but could not prevent against that caused by silencing MEF2A with siRNA. Silencing MEF2A in VE of apoE−/− mice decreased the expression of SIRT1, increased the plasma LDL-c, and abrogated the function of resveratrol on reducing triglyceride. Impaired integrity of VE and aggravated atherosclerotic lesion were observed in MEF2A silenced mice through immunofluorescence and oil red O staining, respectively. In conclusion, resveratrol enhances MEF2A expression, and the upregulation of MEF2A is required for the endothelial protective benefits of resveratrol in vitro via activating SIRT1. Our work has also explored the in vivo relevance of this signaling pathway in experimental models of atherosclerosis and lipid dysregulation, setting the stage for more comprehensive phenotyping in vivo and further defining the molecular mechanisms.